Analisis Struktur Kepemilikan, Profitabilitas Terhadap Nilai Perusahaan Melalui Opini Audit, Stuktur Modal dan GCG sebagai Variabrel Moderasi pada Sub Sektor Perusahaan Food and Beverage yang Terdaftar di BEI - Kristiana Greta Calosa; Hwihanus Hwihanus (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
Abstract. This study aims to analyze the effect of ownership structure, profitability, and capital structure on firm value with audit opinion and Good Corporate Governance (GCG) as moderating variables. The object of this research is a food and beverage sub-sector company listed on the Indonesia Stock Exchange (IDX) during the 2018-2022 period, analyzed using the SmartPLS-based Structural Equation Modeling (SEM) method. The results showed that most of the independent variables did not have a significant effect on firm value. GCG is also not proven to moderate the relationship between these variables and firm value. However, ownership structure has a significant effect on audit opinion, while profitability and capital structure have no significant effect on firm value. This finding indicates the influence of external factors or other variables that have not been tested, so a more comprehensive approach is needed in future research.